(-4x)+6=(-2x)+10

Simple and best practice solution for (-4x)+6=(-2x)+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-4x)+6=(-2x)+10 equation:


Simplifying
(-4x) + 6 = (-2x) + 10

Reorder the terms:
6 + (-4x) = (-2x) + 10

Reorder the terms:
6 + (-4x) = 10 + (-2x)

Solving
6 + (-4x) = 10 + (-2x)

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '(2x)' to each side of the equation.
6 + (-4x) + (2x) = 10 + (-2x) + (2x)

Combine like terms: (-4x) + (2x) = -2x
6 + -2x = 10 + (-2x) + (2x)

Combine like terms: (-2x) + (2x) = 0
6 + -2x = 10 + 0
6 + -2x = 10

Add '-6' to each side of the equation.
6 + -6 + -2x = 10 + -6

Combine like terms: 6 + -6 = 0
0 + -2x = 10 + -6
-2x = 10 + -6

Combine like terms: 10 + -6 = 4
-2x = 4

Divide each side by '-2'.
x = -2

Simplifying
x = -2

See similar equations:

| 20g-16=8(6g+19) | | -(5x-8)-(6x-3)+4=-6(x-4)-(9x+9)+3 | | 5x+(-2)=2x+10 | | -14.18-16.6v=-16.3v-9.68 | | 2x=84-12 | | s+4=7.3 | | -2(n+1)=19+n | | 3(2x+7)=-48+63 | | 2z=-4z-2 | | 3x+30=3x+30 | | (7x-3)+(12x-7)=189 | | -x+6=2x | | 3x-(x+1)=-3+4(x-5) | | -4(x+8)=18-6(x-5) | | 4.5(2r-6)-3r= | | -4+y=-3 | | 1.6x=8.32 | | -3(x+5)=7+12(x-2) | | -4(3-3x)+7x=-37-6x | | 3x-2(7-2x)=10 | | -4=v-9 | | -3(2y-5)=7(y-2) | | 7(x-7)-4=-40-6x | | -(4x-9)-(3x-7)+6=-6(x-9)-(5x+6)+5 | | Y-3=0.4(x+1) | | R+6=-14 | | 5m+0.50=11.50 | | okx^3=343 | | m+0.50=11.50 | | -8+p=6p-6-3p | | 12x+8=8x+(-20) | | 6x-36=6 |

Equations solver categories